Correlation between several anthropometric measurements to birth weight - Muhammad Nur; Noval Azis; Guslihan D. Tjipta; Dachrul Aldy (Paediatrica Indonesiana, 2001)
Perinatal mortality remains one of the factors leading to child mortality, even for crude death as a whole. Therefore, good perinatal care is considered to be useful for reducing this mortality. Low birth weight is one of neonatal morbidity cause; previous studies reported correlation between birth weight to several anthropometric measurements andtheir predictive value. We aimed to evaluate the correlation between birth length, head, chest, abdominal, calf and mid arm circumferences as well as to foot length to birth weight. A cross sectional study was conducted in Adam Malik Hospital Medan between November 1st 1998 to January 31st 1999. All babies without clear moulage, caput succedaneum or cephal hematoma were studied. Birth weight was measured by TANITA weighing scale within the first 24 hours after delivery. Birth length by somatometer and head, chest, abdominal, calf and mid arm circumferences as well as foot length were measured 3 times by using plastic measuring tape. It was evident a positive correlation of birth weight to all such anthropometric measurements with the highest correlation coefficient for calf circumference (r : 0.92). Calf circumference of 9,8 cm is predictor of low birth weight.